Anesthetic management of a child with congenital insensitivity to pain with anhidrosis: A case report - Zhang, Ying; Geng, Zhiyu (Frontiers in Surgery, 2022)
Congenital insensitivity to pain with anhidrosis (CIPA) is a rare, autosomal recessive disease classified as hereditary sensory and autonomic neuropathy type VI (HSAN VI). Patients with CIPA are characterized by insensitivity to pain, episodes of unexplained fever, anhidrosis, self-mutilating behavior, intellectual disability, and autonomic nervous system abnormalities. The clinical features may intrinsically pose anesthetic challenges. We present a case of a patient with CIPA who underwent tumor biopsy under general anesthesia using a laryngeal mask airway (LMA) without any complications. The anesthetic management of this condition is discussed.